Gambaran Karakteristik Demografi dan Tingkat Pengetahuan Lansia yang Aktif dan Tidak Aktif dalam Mengikuti Kegiatan di Posyandu Lansia Pinilih Kelurahan Gumpang Kartasura - Suwandaru, Lugas Dwi, Vinami Yulian, S.Kep., Ns., M.Sc (2016)
Posyandu lansia is a health services for the elderly in the community. Posyandu development receive a positive response from the public but has not been accompanied the increasing by quality of services that have an impact on the level of activity of elderly to participating posyandu. The elderly who active the participating posyandu activities have a better quality of life than the elderly who did not active participating in posyandu activities. While the elderly who did not active in utilizing health services in posyandu, then their medical condition cannot be monitored well. This study aimed to the description of demographic characteristcs and level of knowladge elderly who active and inactive participating Posyandu Pinilih Gumpang Kartasura. This research is a quantitative research. Using a non-experimental research methods with descriptive research design. The sample in this study amounted to 56 elderly. The sample was divided into two categories: the elderly 26 active and 26 inactive elderly who participated in the posyandu with quota sampling technique. Univariate analysis techniques used to reveal the age, sex, occupation and level of knowledge of the elderly following the Posyandu. The survey results revealed that the elderly are active 60-74 year-old, female, junior high school education, it does not work, and good knowledge. While inactive elderly aged 60-74 years, female gender, high school education, not working, and good enough knowledge.